3 sonates pour le piano par Beethoven ... Op: 1er ... No. [1] [i.e. WoO 47, no. 1] - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Paris; France; S. Richault, 2023)
Early edition of the Piano Sonata in E-flat major, WoO 47, no. 1, published by S. Richault in Paris as "Op. 1er, no. 1."